Listing State-Owned Enterprises in Emerging and Developing Economies : Lessons Learned from 30 Years of Success and Failure - World Bank (World Bank, Washington, DC, 2021)
In this report, the authors investigate state-owned enterprise (SOE) listings as a solution to promote local capital markets development. Thus, SOE listings can offer governments an enormous opportunity to kick-start the development of their local capital markets while achieving other divestment objectives, such as harnessing the SOE’s value and raising fiscal revenue. In this report, the authors aim to shed light on this question by investigating emerging and developing economies (EMDE’s) experience with SOE listings over the past 30 years. The authors combine a thorough literature review with a case study analysis of 14 frontier and emerging markets, including interviews with key stakeholders from the public and private sector. In particular, the authors aim to answer the following three questions: (1) what has been the impact of SOE listings on local capital markets development in EMDEs?; (2) what have been the pre-conditions to successfully list a SOE?; and (3) once listed, what have been the drivers for creating a positive impact on capital markets development? Because listings have significant effects on the broader economy and potentially harness the value of SOEs in a different way, this report also attempts to evaluate the impact of SOE listings on other key economic variables - in particular firm performance, the quality of public service delivery, employment, wealth distribution, and fiscal revenue. The sole objective is to provide policymakers with sufficient information to make an educated decision on whether or not SOE listings are a suitable solution for their respective country.